2021
DOI: 10.1080/23311975.2021.1945425
|View full text |Cite
|
Sign up to set email alerts
|

Towards the open eco-innovation mode: A model of open innovation and green management practices

Abstract: Small-and medium-sized enterprises (SMEs) have played an incomegenerating role in economic notions of prosperity in many developed countries, especially Thailand. Inside green economy, fostering eco-innovation by open innovation has become an increasingly new normal issue in Thailand. The ability to identify and collaborate with external knowledge sources and eco-innovative characteristics of SMEs is of essence to policy-makers and firm practitioners. This paper aims to shed the new light on the adoption of op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 99 publications
(120 reference statements)
0
7
0
3
Order By: Relevance
“…In 2021, studies considered open innovation as a driver of organizational performance [154], innovation strategies [155][156][157] and the adoption of eco-innovation [158][159][160].…”
Section: Scientific Production (Rq1)mentioning
confidence: 99%
“…In 2021, studies considered open innovation as a driver of organizational performance [154], innovation strategies [155][156][157] and the adoption of eco-innovation [158][159][160].…”
Section: Scientific Production (Rq1)mentioning
confidence: 99%
“…Thus, intangible assets also generate competitive advantages through the relationship between organizations (Silvestrelli, 2010;Cassetta et al, 2022). The complexity of the adoption of the environmental innovations requires information and knowledge -new or complementary -from the outside of the firm's boundaries (Ghisetti et al, 2015;Casalegno et al, 2020;Valdez-Juárez et al, 2020;Pichlak & Szromek, 2021;Sanchez & Pavez, 2021), involving also a high level of green management practices inside the firm (Naruetharadhol et al, 2021). Indeed, several studies found a positive effect of open innovation -or specific external relationships -on eco-innovation (Ghisetti et al, 2015;Doran & Ryan, 2016;Triguero et al, 2018;Leitão et al, 2020;Valdez-Juárez et al, 2020;Naruetharadhol et al, 2021;Sanchez & Pavez, 2021).…”
Section: Intangible Assets and Eco-innovationsmentioning
confidence: 99%
“…Essa demanda vital incita os setores públicos e privados, de forma compartilhada, a recriarem bens/serviços (englobando a distribuição destes), tecnologias e processos que respeitem o meio ambiente, auxiliando na minimização dos impactos nele desencadeados, na sua restauração e manutenção, além de serem social e financeiramente apropriados (BEISE;RENNINGS, 2003;ELKINGTON, 2012;AFSHARI et al, 2019). As inovações verdes, conforme apontam Hemmelskamp (1996), Kemp e Arundel (1998) e Naruetharadhol et al, (2021), são uma das resoluções que devem ser empregadas nos conflitos ambientais que se alastraram pelo mundo.…”
Section: O Que é Inovação Verde?unclassified
“…Por meio de parcerias firmadas entre as instituições educacionais, a Administração Pública Diretaesferas federais, estaduais e municipais, e as organizações (empresas, ONGs, associações, etc.) vêm gerando projetos de aprendizagem referentes à importância da preservação do meio ambiente, como também, pesquisas voltadas à prevenção dos impactos negativos causados na natureza e manutenção do ecossistema (REID;MIEDIZNSKI, 2008;NARUETHARADHOL et al, 2021). Todavia, muito dos esforços no campo da Administração para se entender o processo de geração de inovações verdes estão centrados nas ações de organizações com fins lucrativos.…”
Section: O Que é Inovação Verde?unclassified
See 1 more Smart Citation